Brand Trust, Social Media, and Repurchase Intention: A Case Study of Le Minerale Consumers in Indonesia - Putra, Wira Pramana; Mukhid, Mukhid; Murthada, Murthada (International Journal of Business, Law, and Education, 2024)
This research investigates the dynamic interplay between brand trust, social media engagement, and repurchase intention, focusing on Le Minerale consumers in Indonesia. Utilizing a case study approach, the study explores the intricate relationships among these factors in the context of the rapidly evolving consumer landscape. The beverage industry, particularly bottled water, serves as the backdrop, with Le Minerale as a prominent brand. Through a comprehensive analysis, the study aims to unravel the factors contributing to brand trust, the role of social media, and their combined impact on consumers' repurchase intentions in the diverse and dynamic Indonesian market.